Peran Financial Performance Sebagai Variabel Intervening pada Pengaruh Intellectual Capital terhadap Firm Value - Irma Dwi Puspitasari (Journal of Economic, Management and Entrepreneurship, 2023)
The purpose of this study is to know the impact of intellectual capital on firm value with financial performance as an intervening variable in banking compenies listed on the Indonesian Stock Exchange (IDX) in 2014-2018. The populations is 44 banks. The sampling techniques used purposive judgement sampling and obtained a research sample of 29 banks. Data analysis techniques used Partial Least Square (PLS). The independent variable is intellectual capital. Intellectual capital is measured by Value Added Intellectual Coefficient (VAICTM). The intervening variable is financial performance which measured by Return On Assets (ROA). The dependent variable is firm value which measured by Price Book Value (PBV). The result show that the intellectual capital have a direct effect on financial performance; intellcectual capital didn’t have direct effect on firm falue; but financial performance was effected on firm value. Financial performance is able to mediate the relation between intellectual capital towards firm value.